IDENTIFIKASI FITOPLANKTON DARI PERAIRAN WADUK NADRA KRENCENG KOTA CILEGON BANTEN - Ambarwati Ambarwati; Saifullah Saifullah; Mustahal Mustahal (Jurnal Perikanan dan Kelautan, 2014)
Inlet of Waduk Nadra affected by the antrophogenic wastes from the domestic activity in surronding area. For the management reason, it is important to do the research in this waters area. The study conducted on June – July 2014 at Waduk Nadra Krenceng, Cilegon Banten. The research used purpossive sampling methods and analyzed by the desctriptive methods. The result showed there were 10 genus of phytoplankton i.e Anabaena sp, Closterium sp, Staurastrum sp, Tetraedron sp, Gloeocystis sp, Desmodesmus sp, Navicula sp, Melosira sp, Gonyostomum sp, and Staurodesmus sp. The most abundant phytoplankton is Anabaena sp and followed by Closterium sp. Total abundance of algae at Waduk Nadra in a range of 6.795 – 16.099 ind/l, where the highest abundance was at station I and the lowest at station III.Keywords: Waduk Nadra, management, phytoplankton